2022
DOI: 10.1111/and.14432
|View full text |Cite
|
Sign up to set email alerts
|

High estradiol level is associated with erectile dysfunction: A systematic review and meta‐analysis

Abstract: Numerous studies conducted to study the role of testosterone in erectile dysfunction (ED) extensively, but less is known of the association between estradiol level and ED. To assess the strong association between estradiol and ED by quantitatively synthesizing all studies evaluating the relationship between estradiol and ED. An extensive literature search was conducted by two authors independently in three electronic databases, including PubMed, Web of Science and Cochrane Library, up to January 10, 2021. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
1
2
1
Order By: Relevance
“…Our research revealed that patients with organic ED had considerably lower estrogen levels. Estrogens play an unidenti ed role in male sexual function, and studies reporting the impact of estrogens on erectile function have been inconsistent (35)(36)(37). The results of our study were signi cantly different from those of previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our research revealed that patients with organic ED had considerably lower estrogen levels. Estrogens play an unidenti ed role in male sexual function, and studies reporting the impact of estrogens on erectile function have been inconsistent (35)(36)(37). The results of our study were signi cantly different from those of previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, serum estradiol levels exhibited signi cant association with ED. This result is consistent with that of a previous metaanalysis, including 1,249 patients with ED and 1,270 healthy individuals 9 . However, the biological mechanisms that link ED with estradiol remain unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Although its antagonistic effect on testosterone through the sympathetic and parasympathetic nervous systems is thought to be one of the mechanisms 27 , testosterone had no effect on ED in the present study. Since estradiol receptors are abundantly expressed in penile tissues 28 , estradiol has been reported to directly impact the erectile function, alongside its effects mediated by testosterone, including an increase in venous vascular permeability via vascular endothelial growth factor, impairment of the corpus cavernosum relaxation, and changes in the structure of the corpus cavernosum 9,29,30 . Although these mechanisms might support our results, drawing a de nitive conclusion is di cult owing to several limitations of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Massachusetts Male Aging Study (MMAS) had revealed that out of 17 investigated hormones only DHEA-S exhibited significant correlation with ED 8 . Additionally, estradiol and prolactin have been reported to affect erectile function 9 , 10 . However, several conflicting results have prevented us from reaching definitive conclusions 11 .…”
Section: Introductionmentioning
confidence: 99%